(untitled) (Federal University Gusau Faculty of Education Journal, 2025)
Over the past two decades, bilateral ties between Nigeria and China have intensified, driven by China’s strategic interest in Africa in general and Nigeria in particular, as well as Nigeria’s quest for trade development through trade expansion, and foreign investment. This paper explores the benefits of this partnership. It looks at the multifaceted relationship between Nigeria and China, emphasizing its implications for national development. Among other issues, the paper examines the historical context of Nigeria-China engagements, emphasizing developmental opportunities and challenges. Drawing on secondary sources and critical content analysis of extant literature as its methodology, the assesses how Nigeria-China relations fosters sustainable national development. The paper concludes by offering policy recommendations aimed at maximizing the benefits of the partnership while mitigating associated risks, emphasizing the need for strategic negotiation, improved governance, and stronger regulatory frameworks.